Vocabulary Learning and Acquisition in English as a Foreign Language: A Case Study (El-Wahat Journal for Research and Studies, 2025)
The present paper is an exploratory research aimed at gaining insights into the vocabulary acquisition strategies used by Algerian students. The research adopted a mixed-method approach to collect data from the respondents. A semi-structured questionnaire was administered to 34 second year students at the department of English language, University of Ghardaia. The results of the study showed that the students used constant techniques to acquire vocabulary, and most of them use dictionaries when searching for new vocabulary. It is recommended that the students use varied strategies and benefit from the information technology items.Keywords: Vocabulary acquisition, Strategies, English as a foreign language, Teaching, Learning.